2010
DOI: 10.1002/ca.20951
|View full text |Cite
|
Sign up to set email alerts
|

Predicting radial nerve location using palpable landmarks

Abstract: The purpose of this study is to predict the location of radial nerve (RN) utilizing palpable anatomic landmarks. Thirty-four paired upper limbs were dissected. The RN was localized: (1) at the humeral spiral groove (SG), (2) lateral intermuscular septum (LIS), and (3) at its' division into the posterior interosseous nerve (PIN) and radial sensory nerve (RSN). The PIN was located at the anterior aspect of the radial neck (AN). Humeral and radial lengths were measured. The RN traversed the SG, on average, 48% (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…Due to the clinical relevance, many anatomic studies have focused on the anatomy of the radial nerve [10][11][12][13][14][15][16]. Carlan et al [15] described the deltoid tuberosity as a potential landmark to determine the location of the radial nerve at the posterior midshaft level of the humerus.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the clinical relevance, many anatomic studies have focused on the anatomy of the radial nerve [10][11][12][13][14][15][16]. Carlan et al [15] described the deltoid tuberosity as a potential landmark to determine the location of the radial nerve at the posterior midshaft level of the humerus.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the location of the radial nerve during the posterior approach to the humerus, and its relationship with a consistent and reliable anatomic landmark, are major concerns for treating surgeons. Another anatomic landmark is needed to consistently and reliably allow the surgeon to locate the radial nerve during this approach, as described relationships [1,[3][4][5][6][7][12][13][14] of the radial nerve with various osseous landmarks rarely hold true in the clinical setting. Therefore, we compared the distance of the radial nerve from the apex of the triceps aponeurosis among cadavers (having an intact humerus) and patients treated with open reduction and internal fixation for distal third humerus fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we describe the relationship of the radial nerve with a proposed soft tissue landmark. Numerous anatomic studies have attempted to establish the relationship of the radial nerve with bony points (lateral epicondyle, medial epicondyle, and angle of acromion) [1,[3][4][5][6][7][12][13][14]. In an anatomic study, Guse and Ostrum [14] reported that the proximal extent of the radial nerve in the spiral groove was 18.1 cm (± 1.1 cm) proximal to the medial epicondyle, whereas the distal extent of the radial nerve in the spiral groove was 12.6 cm (± 1.1 cm) proximal to the lateral epicondyle of the humerus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations